Does CEO duality affect board independence? The moderating impact of founder ownership and family blockholding - Shashank Bansal (Elsevier, 2021)
This study examines the impact of CEO duality on board independence and extends the knowledge by exploring whether the type of firm, the presence of family blockholding, or concentrated founder ownership moderates this impact. The analysis shows that CEO duality improves board independence. The empirical results support the theory of reputation and show that family-owned business group firms encourage board independence if firms have a duality leadership structure compared with non-family business groups, stand-alone, state-owned, and foreign-owned firms. The entrenchment effect of controlling shareholding on board independence overcomes the alignment effect of CEO duality and the results are significant for firms with low information costs and high level of monitoring.